Mobile-Based Decision Support System For Sunday School Student Categorization Using Rule-Based Method And RAD Model - Tan, Andreas; Putri, Sri Rama (Jurnal Teknologi Informasi Universitas Lambung Mangkurat (JTIULM), 2026)
The manual determination of student categories at Sunday School based on attendance records is prone to human error, time-consuming, and lacks consistency in evaluation. This study develops a mobile-based Decision Support System (DSS) to automate student categorization using attendance percentages. The system employs a Rule-Based approach with explicit logical thresholds and is developed using the Rapid Application Development (RAD) model to ensure rapid prototyping, iterative refinement, and active user involvement. Key features include QR-based attendance tracking, real-time percentage calculation, automated categorization (Very Diligent, Diligent, Fairly Diligent, Needs Attention), and PDF report generation. Black-box testing confirms that all functional modules perform as expected, achieving a 100% validation rate across core scenarios. The system successfully improves data accuracy, reduces administrative workload, and provides objective, transparent recommendations for student recognition and follow-up coaching. This solution demonstrates the practical applicability of rule-based DSS in religious educational institutions seeking efficient, data-driven student evaluation.